PRENUPTIAL AGREEMENTS AS INSTRUMENTS FOR PROTECTING PROPERTY RIGHTS: HARMONIZING ISLAMIC LAW AND HUMAN RIGHTS - Mahesa Feby Leandi; Siti Zumrotun (MADDIKA : Journal of Islamic Family Law, 2026)
Prenuptial agreements have generally been understood as instruments for regulating marital property; however, studies that integrate the protection of property rights from a human rights perspective with the principles of Islamic family law remain relatively limited. This study offers a novel perspective by reconstructing the philosophical foundation of marital property agreements as instruments for safeguarding individual property rights while promoting distributive justice within the family. It aims to examine the philosophical underpinnings of marital property agreements in securing individual property rights under Islamic Family Law and to analyze the juridical implications of the expanded legal scope of such agreements following Constitutional Court Decision No. 69/PUU-XIII/2015 which aims to protect of the property rights of spouses. This study employs doctrinal legal research using statutory, conceptual, and philosophical approaches. The legal materials consist of legislation, judicial decisions, classical and contemporary Islamic legal literature, international human rights instruments, and relevant scholarly publications. The findings demonstrate that marital property agreements are not inconsistent with the Islamic legal principle of infiṣāl al-dhimmah al-māliyyah. Rather, they are consistent with the objectives of maqāṣid al-sharīʿah, particularly ḥifẓ al-māl and sadd al-dharāʾiʿ, serving as preventive legal mechanisms to safeguard property rights and minimize potential disputes within the family. Furthermore, Constitutional Court Decision No. 69/PUU-XIII/2015 has broadened legal protection by recognizing the validity of postnuptial agreements, thereby providing married couples with greater legal autonomy to protect their personal assets from civil risks, including bankruptcy and third-party asset seizure. This legal development reinforces the human right to private property while preserving the principle of justice within marital relationships. The study further demonstrates that marital property agreements constitute legitimate and strategic preventive legal instruments for protecting individuals' economic rights while maintaining a fair balance of rights and obligations between spouses. These findings underscore the importance of enhancing public understanding of marital property agreements as an integral component of legal protection and human rights within the institution of marriage.